Sampling of Rhyssomatus subtilis (Coleoptera: Curculionidae) adults on soybean, using the vertical beat sheet method - Cazado, Lucas Emiliano (2013)
Rhyssomatus subtilis Fiedler (Coleoptera: Curculionidae) adults were sampled in 10 soybean crop fields in Northwestern Argentina throughout 2012 and 2014, using the vertical beat sheet (VBS) method. The obtained values were contrasted with the total number of adults actually present in those fields, which demonstrated that the abovementioned method caught 60% of individuals. Therefore, it became evident that these data needed to be corrected by dividing the values obtained with VBS by 0.65, number obtained with a linear regression analysis.